Consumers' purchase intention of 3D-printed apparel. Issue 4 (1st October 2016) - Perry, Anna
Abstract: The purpose of the current study is to address how perceived product characteristics (e.g. compatibility, aesthetics), consumers' confidence (e.g. self-efficacy) and attitude, and social influence (e.g. subjective norm) influence purchase intention of 3D-printed apparel. A total of 1002 US participants were recruited. The results indicated that purchase intention was mostly determined by a favorable attitude, moderately determined by a characteristic of the product (compatibility), and limitedly determined by the social influence (subjective norm). In addition, a positive attitude was largely determined by aesthetics and compatibility of 3D-printed apparel, moderately determined by self-efficacy, and limitedly contributed by social influences. Therefore, as an innovative product that has not yet been widely spread in the market, consumers' attitudes toward 3D-printed apparel were mostly determined by the product itself: whether it is aesthetically pleasing, and whether it is suitable for consumers' lifestyle and needs. Consumers' confidence in using the product moderately and social influences limitedly contributed to a favorable attitude. This study filled a research gap about consumers' purchase intentions of 3D-printed apparel. This study also provided important insights for the apparel industry to effectively create and promote 3D-printed apparel in future.